Faktor Yang Mempengaruhi Nilai Perusahaan Manufaktur Yang Terdaftar Di BEI - Shierra Hendro Jaya, Merry Susanti (Jurnal Paradigma Akuntansi, 2019)
The purpose of this research was to obtain empirical evidence whether or not variables of profitability, firm size, liquidity, leverage, and board of independent commissioners have significant impacts on the firm value. Population of this research is manufacturing companies, which listed in BEI at period 2015-2017, as many as 59 companies (117 sampels) using the purposive sampling method. This research was conducted by means of multiple regression linear analysis with the help of a computer programme of SPSS version 20.0. The result of this research conducted partially from 2015 to 2017 is that profitabilitiy, size and board of independent commissioners proved to have a positive effect on firm value but liquidity and leverage have no significant effect on firm value